Konsep Khalifah menurut Tafsir Al-Mishbah - Saifayurallah Saifayurallah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2016)
This study aims to determine the use of the term caliph in the Qur'an. By using the thematic method, the writer finds that the word caliph is found in al-Baqarah verse 30 and Shad verse 26. In terms of language, the term Khalifah consists of three letters, namely kha ', lam and fa. The meaning contained in it there are three kinds, namely, changing position, later, and change. From this word, two different forms of the verb are found in the Qur'an, namely khalafa-yakhlifu which is used to mean